Health psychological constructs as predictors of doping susceptibility in adolescent athletes - Blank, C.; Schobersberger, W.; Leichtfried, V.; Duschek, S. (Asian Journal of Sports Medicine, 2016)
Background: Doping is a highly relevant problem in sport, even in adolescent athletes. Knowledge of the psychological factors that influence doping susceptibility in young elite athletes remains sparse.